FLORAL EXTRACTS OF ALLAMANDA BLANCHETII AND ALLAMANDA CATHARTICA ARE COMPARATIVELY HIGHER RESOURCE OF ANTI-OXIDANTS AND POLYSACCHARIDES THAN LEAF AND STEM EXTRACTS - Ghosh, Chandreyi; Banerjee, Sayantan (International Journal of Current Pharmaceutical Research, 2018)
Objective: The present study undertakes a comparative analysis of the level of secondary metabolites present in the leaf, flower and stem of the two ornamental plants, Allamanda blanchetii and Allamanda cathartica. Methods: The two plant species, Allamanda blanchetii and Allamanda cathartica were collected, washed, shade dried in room temperature and powered in mechanical grinder. Phytochemicals were extracted from the power with methanol and double distilled water. The estimation of flavonoids, polyphenols, polysaccharide were done by standard methods and the anti-oxidant activity was measured by 1,1-diphenyl-2-picrylhydrazyl (DPPH) discoloration assay. Results: Our study reveals that the flower of both species contain highest amount of secondary metabolites in crude methanolic and aqueous extracts. In case of leaf, the methanolic extracts contain higher amount of polyphenol, flavonoid and anti-oxidant property in comparison to aqueous extracts, where as the aqueous extract contain higher amount of polysaccharide content than its counterpart. In stem, crude organic extract has higher amount of polyphenol and flavonoid and the aqueous extract has higher amount of polysaccharide and anti-oxidant property. Conclusion: The flower of Allamanda cathartica and Allamanda blanchetii has higher amount of flavonoids, polyphenols, polysaccharide and the floral extracts display comparatively higher anti-oxidant property.